Games on the seashore of Salalah: the discovery of mancala games in Dhofar, Sultanate of Oman - Charpentier, Vincent; de Voogt, Alex; Crassard, Rémy; Berger, Jean-François; Borgi, Federico; Mashani, Ali al- (Arabian Archaeology and Epigraphy, 2014)
During the 2013 ﬁeldwork of the French archaeological mission along the shores of the Arabian Sea, mancala games were discovered on the seashore of Salalah at the site of Ad-Dahariz. They are cup-hole carvings made directly into rock slabs and distributed in six distinct zones of the site. They usually consist of fourteen cup-holes aligned in two lines of seven, two supplementary holes being sometimes present on each side. They are the ﬁrst of their kind in South Arabia and can be compared to similar conﬁgurations of carved games elsewhere in Arabia, such as at Jebel al-Jassasiya, Qatar. This paper presents the potential origins of this game in the region, as well as a plausible dating of their use.
Keywords: Archéologie – Oman; Dhofar